Happiness and Health Behaviours in Chilean College Students: A Cross-Sectional Survey - Vera-Villarroel, P; Kuhne-Covarrubias, W (2011)
Background: Happiness has been associated with a range of favourable health outcomes through two pathways: its relationship with favourable biological responses to stress and with healthy lifestyles and prudent health behaviours. There are a substantial number of cross-cultural studies about happiness, but none of them has studied the association of happiness with perceived stress and health behaviours in Latin American samples. Therefore, the aim of this study was to examine the association between general happiness and these variables in a Latin American sample. Methods. We conducted a survey to examine the status of 3461 students aged between 17 and 24 years old (mean age = 19.89; SD = 1.73) who attended University of Santiago de Chile during 2009. The healthy behaviours indexes assessed were the frequency of daily physical exercise, fruits/vegetables intake, breakfast and lunch intake, smoking, alcohol and other drugs consumption. We also included the assessment of perceived stress and Body Mass Index. All of them were evaluated using a self-report questionnaire. Results: The univariate and multivariate binary logistic regression analyses showed that being female and younger was related to a higher happiness, as well as that people self-reporting daily physical activity, having lunch and fruits and vegetables each day had a higher likelihood (OR between 1.33 and 1.40) of being classified as "very happy". Those who informed felt stressed in normal circumstances and during tests situations showed a lower likelihood (0.73 and 0.82, respectively) of being considered "very happy". Regarding drug consumption, taking tranquilizers under prescription was negative related to "subjective happiness" (OR = 0.62), whereas smoking was positive associated (OR = 1.20). Conclusions: The findings of this study mainly support the relationship between happiness and health outcomes through the two pathways previously mentioned. They also underscore the importance of that some healthy behaviours and person s cognitive appraisal of stress are integrated into their lifestyle for college students. Additionally, highlight the importance of taking into account these variables in the design of strategies to promote health education in university setting. © 2011 Piqueras et al; licensee BioMed Central Ltd.